Thermal Pre-treatment Techniques for Extraction of Nickel and Cobalt from Western Australia Saprolite Ores - Pulgarin Saenz, John Alexander (Curtin University, 2024)
Laterite deposits, holding 70% of global nickel resources, are economically challenging to process but are gaining interest. Traditional methods like high-pressure acid leaching (HPAL) face difficulties with saprolite ores due to high magnesium silicates. This research explores alternative methods: non-reductive roasting followed by ammonia glycine leaching and reductive roasting to concentrate nickel and cobalt into a ferronickel phase. High goethite samples showed improved leachability, while magnesium silicate-rich samples required high-temperature reductive roasting with controlled CO2 flow and sodium chloride addition for optimal ferronickel recovery. FactSage® simulations highlighted discrepancies between predicted and experimental results due to kinetics and mass transfer constraints.